ISLAMIC RELIGIOUS EDUCATION LEARNING MANAGEMENT TO ENHANCE STUDENT LEARNING CONCENTRATION AT SMAN 14 GARUT - Farah Hanifah; Yufi Mohammad Nasrullah; Fiqra Muhamad Nazib; Masripah (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This research seeks to explain the implementation of learning management in the Islamic Religious Education (PAI) subject and its impact on students’ concentration at SMAN 14 Garut. The study uses a qualitative descriptive approach, collecting data through triangulation methods, including observations, interviews, and document analysis. The findings indicate that PAI teachers have implemented all stages of learning management in a structured manner, from developing lesson plans and organizing the classroom to conducting teaching and learning activities and carrying out learning evaluations. The lesson plans were designed based on students’ characteristics to foster a comfortable, supportive learning environment. Learning methods that actively involve students were also found to reduce boredom and encourage greater participation, enabling students to maintain their focus throughout the learning process. Routine evaluations help teachers identify and address weaknesses in teaching and learning. Overall, effective learning management contributes significantly to improving students’ concentration during learning and supports the creation of more effective PAI instruction.